2021
DOI: 10.1038/s41467-021-21493-w
|View full text |Cite
|
Sign up to set email alerts
|

Layer number dependent ferroelasticity in 2D Ruddlesden–Popper organic-inorganic hybrid perovskites

Abstract: Ferroelasticity represents material domains possessing spontaneous strain that can be switched by external stress. Three-dimensional perovskites like methylammonium lead iodide are determined to be ferroelastic. Layered perovskites have been applied in optoelectronic devices with outstanding performance. However, the understanding of lattice strain and ferroelasticity in layered perovskites is still lacking. Here, using the in-situ observation of switching domains in layered perovskite single crystals under ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
(32 reference statements)
0
37
0
Order By: Relevance
“…Furthermore, the effects of 3D stacking on such 2D ferroelasticity, such as surface wrinkles and inclined DWs, have also been revealed explicitly in 3R β’ -In 2 Se 3 . We note that during the review process of this work, 2D ferroelasticity is also reported in layered perovskites 32 , but only limited to crystals ~10 micron thick in contrast to the 2D flakes down to few-layer thickness investigated in our work. The demonstrated 2D ferroelasticity in both works further indicates its wide presence in vdW materials with anisotropic lattice strain, such as the 1T’ TMDs with Peierls distortion 1 , 17 , 28 , 52 , 56 and 2D ferroelectrics such as the SnTe family 13 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the effects of 3D stacking on such 2D ferroelasticity, such as surface wrinkles and inclined DWs, have also been revealed explicitly in 3R β’ -In 2 Se 3 . We note that during the review process of this work, 2D ferroelasticity is also reported in layered perovskites 32 , but only limited to crystals ~10 micron thick in contrast to the 2D flakes down to few-layer thickness investigated in our work. The demonstrated 2D ferroelasticity in both works further indicates its wide presence in vdW materials with anisotropic lattice strain, such as the 1T’ TMDs with Peierls distortion 1 , 17 , 28 , 52 , 56 and 2D ferroelectrics such as the SnTe family 13 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 61%
“…2D ferroelasticity has also been predicted in monolayer 1T’ transition metal dichalcogenides (TMDs) based on first-principles calculations 28 , 29 , which may couple with other extraordinary properties to realize strain-tunable functionalities and 2D multiferroics 4 . However, despite several proposed 2D ferroelastic behavior 28 31 and one very recent demonstration on micron-thick layered perovskites 32 , 2D ferroelasticity evidenced by the mechanical switch of spontaneous lattice strain in ultrathin vdW materials has not yet been validated experimentally 4 .…”
Section: Introductionmentioning
confidence: 98%
“…Apart from the 3D confinement achieved in perovskite QDs, another strategy to attain high luminescent quantum yields at relatively low excitation intensities is to confine the volume of the perovskite crystal in 1D to create 2D and quasi-2D perovskites. [10,23,55,57,86,140,153] The crystal structure of the 2D MHPs commonly belongs to the Ruddlesden-Popper (RP) phases. Compared to 3D perovskites, 2D perovskites have higher exciton binding energy because of the quantum confinement effects along the thickness direction and lower dielectric constants due to the larger fraction of organic components.…”
Section: D and Quasi-2d Perovskitesmentioning
confidence: 99%
“…Apart from the 3D confinement achieved in perovskite QDs, another strategy to attain high luminescent quantum yields at relatively low excitation intensities is to confine the volume of the perovskite crystal in 1D to create 2D and quasi‐2D perovskites. [ 10,23,55,57,86,140,153 ]…”
Section: Mhp Structures and Their Luminescent Propertiesmentioning
confidence: 99%
“…Due to the chemical diversity of organic spacer cations, metal ions, and halide anions and their absorption/emission properties and photochemical stability, two-dimensional (2D) organic-inorganic perovskites have emerged for photodetectors, [1,2] optoelectronic, [3][4][5][6] lasers, [7][8][9] electroluminescence, [10,11] and spintronics. [12][13][14] Multiple quantum well structures of twodimensional (2D) perovskite materials, in which inorganic octahedra networks are alternately stacked with organic cation spacers, offer them an ideal platform for structural diversity and novel functionalities.…”
Section: Introductionmentioning
confidence: 99%